2005
DOI: 10.1155/2005/198387
|View full text |Cite
|
Sign up to set email alerts
|

A Sampling of Canadian Practice in Managing Nonvariceal Upper Gastrointestinal Bleeding before Recent Guideline Publication: Is there Room for Improvement?

Abstract: Compared with recommendations put forward in the new guidelines, clinical practice before guideline publication was variable. The future level of guideline adherence and patient outcome data should be quantified and monitored as the guidelines are disseminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Despite their derivation over a decade ago, external validation in multiple cohorts and recommendations in evidence-based national and international guidelines,8 data from Canada and the UK show poor adherence to their use. In the Canadian RUGBE study, one out of 15 sites used the Rockall score routinely and explicitly to stratify patients with NVUGIB and none routinely used the GBS 17. Subsequently, in the REASON-2 study only one of 826 patients across 43 participating sites was found to have a Rockall or GBS score documented in the medical records 11.…”
Section: Risk Stratification Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their derivation over a decade ago, external validation in multiple cohorts and recommendations in evidence-based national and international guidelines,8 data from Canada and the UK show poor adherence to their use. In the Canadian RUGBE study, one out of 15 sites used the Rockall score routinely and explicitly to stratify patients with NVUGIB and none routinely used the GBS 17. Subsequently, in the REASON-2 study only one of 826 patients across 43 participating sites was found to have a Rockall or GBS score documented in the medical records 11.…”
Section: Risk Stratification Scoresmentioning
confidence: 99%
“…These considerations may explain why, in practice, there appears appropriately to be uncertainty among clinicians as to the usefulness of PPIs before endoscopy. In the UK audit, 43% of patients presenting with all-cause UGIB were prescribed a PPI before endoscopy,14 67% in the Italian PNED-1 registry were prescribed a PPI either during the emergency room visit or hospitalisation12 and, in the RUGBE database, 47% of participating sites routinely started a high-dose PPI before endoscopy 17. These uncertainties and variation in practice suggest that further research is needed to evaluate the role of these agents prior to endoscopy.…”
Section: Pharmacological Treatment Before Endoscopymentioning
confidence: 99%
“…Only 37% of hospitals had an emergency endoscopy nurses' rota. There is thus a need to increase after-hours availability for the expert delivery of early endoscopy as currently recommended by guidelines, a finding also noted in other countries45 46; perhaps even more disturbing was the realisation that only 41% (666/1640) of first endoscopies performed by trainees were performed under supervision.…”
Section: What Does the Study By Hearnshaw Et Al5 Add To Our Knowledge?mentioning
confidence: 98%
“…Various professional society guidelines advocate using the GBS to identify low risk patients [2, 12 -14], and an international consortium on the management of non-variceal UGIB proposed risk stratification of patients as a quality indicator [15]. However, the use of scoring tools for the triage and management of UGIB is uncommon in practice; one national audit demonstrated the complete absence of its systematic use [16].…”
mentioning
confidence: 99%